Şevket Bulut'un "Kuyruğu Kesilen At" Hikayesi - Safi, İhsan (Gökkubbe, 2008)
Bu makalede, son dönem Türk hikayecilerinden Şevket Bulut'un Al Karısı adlı kitabında yer alan "Kuyruğu Kesilen At" hikayesi incelendi. "Kuyruğu Kesilen At" hikayesi, Şevket Bulut'un diğer hikayelerindeki özelliklerin birçoğunu taşımakla birlikte, zaman zaman onlardan farklılıklar da göstermektedir. Konusu, Maraş'ın Elbistan ilçesinde geçmektedir. Aleviler içerisinde meydana gelen bir hadise anlatılmakta, onların namuslarına son derece düşkün oldukları verilmek istenmektedir. In this article, the short story called "The Horse whose Tail was cut" founding in the book of Al Karısı written by Şevket Bulut being a contemporary narrator of Turkish literature is examined. This is one of the Şevket Bulut's short stories where he successfully uses folkloric materials collected by him from where he visited during his official trips. Although "The Horse whose Tail was cut" carries a number of similar characterıstics with Şevket Bulut's other stories, it to some extent differs from those stories, too. Its topic and events take place in the town of Elbistan of Maraş. In this story, Şevket Bulut narrates an incident that has been occurred in an Alevid community. By narrating his story, Bulut tries to depict how they were devoted to their decency.
Keywords: Şevket Bulut; Hikaye Tahlili; Günümüz Türk Hikayeciliği; Alevilik; Story Analyses; Today's Turkish Narration; Alevidizm (Shiism)